IoT Based Electrical Monitoring System Using PZEM Sensor: Sistem Pemantauan Listrik Berbasis IoT Menggunakan Sensor PZEM - Cahyo Budiarso; Arief Wicaksono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Electrical energy monitoring is essential for ensuring efficient energy usage and system reliability in modern environments. Specific Background The integration of Internet of Things technology enables real-time monitoring of electrical parameters such as voltage, current, and power. Knowledge Gap However, existing systems often lack integrated monitoring platforms with reliable data transmission and accessible interfaces. Aims This study aims to design and implement an IoT-based electrical monitoring system using sensor modules and microcontroller platforms. Results The developed system successfully monitors electrical parameters and transmits data in real-time to a user interface, demonstrating functional performance under testing conditions. Novelty The system integrates sensor-based measurement with IoT communication and user-friendly monitoring interface in a unified framework. Implications The results provide a practical solution for real-time electrical monitoring and support further development of smart energy management systems. Keywords: IoT Monitoring, Electrical Parameters, PZEM Sensor, Energy Monitoring, Smart System Key Findings Highlights Real-time measurement achieved through integrated sensor system Data transmission enables remote monitoring capability System architecture supports scalable implementation